2022
DOI: 10.3171/2021.3.spine202056
|View full text |Cite
|
Sign up to set email alerts
|

Acute, severe traumatic spinal cord injury: improving urinary bladder function by optimizing spinal cord perfusion

Abstract: OBJECTIVE The authors sought to investigate the effect of acute, severe traumatic spinal cord injury on the urinary bladder and the hypothesis that increasing the spinal cord perfusion pressure improves bladder function. METHODS In 13 adults with traumatic spinal cord injury (American Spinal Injury Association Impairment Scale grades A–C), a pressure probe and a microdialysis catheter were placed intradurally at the injury site. We varied the spinal cord perfusion pressure and performed filling cystometry. P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The full data extraction table for all 73 included articles is provided on the Open Science Framework. These articles consisted 34 original research articles, 6 , 8 , 9 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 13 conference abstracts, 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 13 literature reviews, 24 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 4 systematic reviews, 5 , 13 , 14 , 15 4 letters to the editor, 76 , 77 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The full data extraction table for all 73 included articles is provided on the Open Science Framework. These articles consisted 34 original research articles, 6 , 8 , 9 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 13 conference abstracts, 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 13 literature reviews, 24 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 4 systematic reviews, 5 , 13 , 14 , 15 4 letters to the editor, 76 , 77 , ...…”
Section: Resultsmentioning
confidence: 99%
“…Phang and colleagues concluded that monitoring from the injury site is safe and this was concurred by the systematic review of Menacho & Floyd (2021). 14 More recent studies have reported the incidence of pseudomeningocele to be as high as 54% (7/13) 24 and CSF leak in 19% of patients (5/26). 44 Only two original research articles have addressed adverse events related to lumbar ITP monitoring.…”
Section: Resultsmentioning
confidence: 99%
“…The Effects of SCPP Support on Adverse Events. This update included four new studies, [28][29][30]46 which were considered in addition to four from the prior review. 32,36,42,45 According to…”
Section: Smentioning
confidence: 99%
“…Asymptomatic pseudomeningocele occurred in 7/13 (54%) ISCoPE patients where the intrathecal catheter was inserted intra-operatively at the site of the SCI. 29 The quality of the evidence was rated down due to study design, risk of bias, indirectness, and inconsistency, and imprecision.…”
Section: Very Low Study Design Risk Of Bias Indirectness Imprecisionmentioning
confidence: 99%
“…Intraspinal pressure and spinal cord perfusion pressure are clinically important parameters that correlate with injury site metabolism (8) and long-term outcome (9). Interventions to increase spinal cord perfusion pressure improve somatosensory (10) and motor-evoked (11) responses at the injury site, increase limb motor score (11, 12), lower the sensory level (13), and improve urinary (14) and anal sphincter (15) functions.…”
mentioning
confidence: 99%